2017
DOI: 10.1037/apl0000197
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ responses to an organizational merger: Intraindividual change in organizational identification, attachment, and turnover.

Abstract: The authors used pre-post merger data from 599 employees experiencing a major corporate merger to compare 3 conceptual models based on the logic of social identity theory (SIT) and exchange theory to explain employees' merger responses. At issue is how perceived change in employees' own jobs and roles (i.e., personal valence) and perceived change in their organization's status and merger appropriateness (i.e., organizational valence) affect their changing organizational identification, attachment attitudes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 242 publications
2
39
0
1
Order By: Relevance
“…However, there is also another approach (e.g. Boivie et al, 2011;Sung et al, 2017;Ullrich et al, 2005, for examples on mergers) that uses qualitative methods or surveys to measure social identification. Future research should therefore seek to complement our results by measuring organizational identification directly using qualitative or mixed methods to obtain a more fine-grained analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also another approach (e.g. Boivie et al, 2011;Sung et al, 2017;Ullrich et al, 2005, for examples on mergers) that uses qualitative methods or surveys to measure social identification. Future research should therefore seek to complement our results by measuring organizational identification directly using qualitative or mixed methods to obtain a more fine-grained analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As organizational identity is key to understanding strategic change (Ravasi & Phillips, 2011), decision making (Gioia & Thomas, 1996;Riantoputra, 2010), and organizational practices (Clark & Geppert, 2011), acquisitions have been increasingly recognized as trigger events for identity change at both the individual and organizational level of analysis (Giessner, Horton & Humborstad, 2016;Lupina-Wegener, Schneider & van Dick, 2015). Identity issues in acquisitions have received substantial attention, with scholars mainly focusing on individual identification following an acquisition (Spoor & Chu, 2017;Sung et al, 2017;Ullrich et al, 2005;van Dick et al, 2006;van Knippenberg et al, 2006), occupational identification (Kroon & Noorderhaven, 2018), or leaders' identity work (Xing & Liu, 2016). We concentrate on the firm level, at which organizational identity issues are expected to affect both the acquisition and integration processes.…”
Section: Acquisitions As Organizational Identity Change Trigger Eventsmentioning
confidence: 99%
“…To cope up to the business needs of growth and profitability and get the advantage of economies of scale, firms are increasingly entering new territories and industries by mergers and acquisitions (Graebner et al, 2017; Kroon & Noorderhaven, 2018). Despite their increasing frequency, studies have shown that mergers and acquisitions are not able to obtain the desired results (Sung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, employee resistance appears to be a major factor in the overall success of this strategic move. The purpose of this paper, three part, is to provide a thorough overview of the forces at play in employee resistance to change, its influence on the M&A’s success, and the ways to address such resistance (van Dijk & van Dick, 2009), cultural factors (Pablo, 1994; Stahl & Voigt, 2008; Weber et al, 1996), organisational identification (Kroon & Noorderhaven, 2018), lack of communication (Appelbaum et al, 2017; Zagelmeyer et al, 2018), problem in the integration phase (Calipha et al, 2010), job insecurity among employees (Sung et al, 2017) and a lot more. Despite all these efforts to pinpoint the root causes of failure and suggestion of ways to improve the same, the exact factors that might predict the success or failure of a merger or an acquisition remain unclear.…”
Section: Introductionmentioning
confidence: 99%